South Yorkshire Accent in Films: A Phonological Transformation?” - Pérez Vázquez, Ángela (Journal of Artistic Creation and Literary Research, 2025)
The Yorkshire English variety is without doubt one of the best-known regional accents along with Cockney, Scouse and Geordie. The present paper formulates the hypothesis that the broadness of the Yorkshire dialect has decreased throughout the years, tending to a more standardised English. In order to illustrate this process of transformation, the article offers a qualitative study of the phonological features prominent in three films by Ken Loach, Kes (1969), Looks and Smiles (1981) and The Navigators (2001), all representatives of the Yorkshire variety. The article also includes a phonological transcription of the scenes that have been selected.